Evolutionary states of the two shortest period O-type overcontact binaries V382 Cyg and TU Mus - Qian, S.-B. (2007)
Up to now, V382 Cyg and TU Mus are the only two discovered O-type overcontact binary stars with periods less than two days (P = 1.8855 and 1.3873 d). Both systems contain a visual companion. New eclipse times and analyses of orbital period variations of the two systems are presented. It is discovered that the periods of both binaries show cyclic oscillations with periods of 47.70 and 47.73 yr, while they undergo continuous increases at rates of dP/dt = +4.4 × 10−7 and +4.0 × 10−7 d yr−1, respectively. The periodic variations can be interpreted as light travel times effects caused by the presence of invisible tertiary components suggesting that they may be quadruple systems. It is possible that the additional bodies may play an important role in the formation and evolution of the two massive overcontact binaries by removing angular momentum from the central systems, and causing the eclipsing pairs to have lower angular momentum and shorter initial orbital periods. In this way, the original detached systems can evolve into the present overcontact configurations via a Case A mass transfer. This is in agreement with the observed long-term period increase of V382 Cyg and TU Mus, which can be explained by mass transfers from the less massive components to the more massive ones. It is found that the time-scales of the long-term period variations of both systems are much longer than the thermal time-scales of the secondary components, but are close to their nuclear time-scales. This suggests that the two massive binaries have been through the rapid mass-transfer evolutionary stage on the thermal time-scales of the secondaries, and they are now on the slow phase of Case A mass transfer. It is shown that massive overcontact binaries are going through a short-lived overcontact configuration during the evolutionary phases of Case A mass transfer, which is different from the situation of late-type overcontact binary stars where components remain in good overcontact configuration driving by a combination of thermal relaxation oscillation and variable angular momentum loss via change in overcontact depth. This conclusion is in agreement with the distribution of overcontact binary stars along with the orbital period.